2021
DOI: 10.1080/00365521.2021.1879245
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study on time trends of hemoglobin in primary care comparing prediagnostic colorectal cancer patients vs age- and sex-matched controls

Abstract: Olsson (2021): A population-based study on time trends of hemoglobin in primary care comparing prediagnostic colorectal cancer patients vs age-and sex-matched controls, Scandinavian Journal of Gastroenterology,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Another study observed a significant correlation between very advanced CRC, compared with locally advanced, in terms of anemia, tumor size and presentation of any symptoms before diagnosis [63]. The study by Li et al consolidates the usefulness of time trends in Hb prior to diagnosis in CRC and questions whether the use of these algorithms could influence the distribution of CRC stages [59]. All these studies have compared patients with CRC and controls without this pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study observed a significant correlation between very advanced CRC, compared with locally advanced, in terms of anemia, tumor size and presentation of any symptoms before diagnosis [63]. The study by Li et al consolidates the usefulness of time trends in Hb prior to diagnosis in CRC and questions whether the use of these algorithms could influence the distribution of CRC stages [59]. All these studies have compared patients with CRC and controls without this pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that a higher anemia prevalence of up to 71.1% was observed in the CRLM group compared to 52.8% in the CRC group in the three months prior to CRC diagnosis (Table 1). The etiology of anemia is diverse, and its Positive Predictive Value (PPV) for CRC in primary care is only 1-2% [58,59]. In addition, even though 60% of patients with iron deficiency anemia do not have a related cause, endoscopic exploration would be justified as they are at higher risk of suffering CRC [60].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, it is possible that FIT should not be used in symptomatic patients with anaemia, in order to avoid false-negative outcomes. This is a key aspect of a potential use of FIT amongst symptomatic patients as approximately some 40% of CRC patients overall are expected to be anaemic at the time of diagnosis [ 16 , 17 ]. Thorough knowledge on the accuracy of FIT, specifically in patients with either anaemia or amongst those who report rectal bleeding, is a decisive aspect on the potential use of FIT in symptomatic patients, in particular for symptomatic patients presenting in primary care.…”
Section: Introductionmentioning
confidence: 99%